1995
DOI: 10.1142/s0217984995000619
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a Nondegenerate Two-Photon Jaynes–cummings Model

Abstract: A generalized Jaynes–Cummings model including the Stark shifts is investigated where the transition is mediated by two different modes of photons. For two different types of correlated field states, the pair coherent states and two-mode SU(1, 1) coherent states, the effect of including the Stark shift on the dynamical behavior of atomic inversion, atomic squeezing parameters, second order coherence function, and photon number distribution is investigated. Our results indicate significant changes in the behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some similarities in the Rabi frequencies of both con®gurations for some special conditions of the parameters were reported [14], and the connection between these con®gurations was deeply studied in [24]. It was reported that for the ¥ [25,26] and ¤ [27,28] models, when making the adiabatic approximation, the appearance of Stark shifts must be taken into account. In [24] the Stark shifts were neglected in order to separate their contribution to the nontrivial dynamics studied.…”
mentioning
confidence: 96%
“…Some similarities in the Rabi frequencies of both con®gurations for some special conditions of the parameters were reported [14], and the connection between these con®gurations was deeply studied in [24]. It was reported that for the ¥ [25,26] and ¤ [27,28] models, when making the adiabatic approximation, the appearance of Stark shifts must be taken into account. In [24] the Stark shifts were neglected in order to separate their contribution to the nontrivial dynamics studied.…”
mentioning
confidence: 96%